The Nexus between Energy, Environment and Growth: Evidence from Latin-American Countries - Razzaq, Naveed; Muhammad, Faqeer; Karim, Rehmat; Tariq, Muhammad; Muhammad, Khair (International Journal of Energy Economics and Policy, 2020)
The purpose of this research is to explore the association among energy, environment and economic growth in Latin-American countries from 1990-2014 by using multivariate Structure. This study used number of co-integration techniques to confirm log run relationship among environment, and energy. It study findings also shows the effect of the energy on environment in the long run by using FMOLS and DOLS. In addition, this research also employed the causality test to study the causal relation among the variables. The outcomes of the various tests of co-integration endorse a long-run relationship among REN and NREN consumption and environment. The long run results show that the use of renewable energy source can reduce the CO2 emissions in selected countries. Moreover, the non-renewable energy consumption is increasing CO2 emissions. In addition, the direction of the causality is unidirectional from REN to CO2, NREN to CO2 and GDP to CO2. However, there is absence of two-way causality among the variables in the model. Keywords: Energy, Panel Co-integration, CO2 Emissions, Economic Growth JEL Classifications: F21, O44, Q43 DOI: https://doi.org/10.32479/ijeep.9933